LiDAR-based glacial geomorphological dataset, southern sector of Baltic Ice Stream Complex, last Scandinavian Ice Sheet, Poland - Izabela, Szuman; Z, Kalita Jakub; W, Ewertowski Marek; D, Clark Chris; J, Livingstone Stephen (Zenodo, 2021)
This GIS dataset contains results of glacial geomorphological mapping of central west Poland based on a 0.4 m high-resolution Digital Elevation Model derived from airborne Light Detection and Ranging data. The mapped area covers area of 65 000 km 2 located along the southern sector of the last Scandinavian Ice Sheet within the limits of the terrestrially terminating Baltic Ice Stream Complex. The GIS dataset contains 5461 features in GeoPackage format that represent: Mega-Scale Glacial Lineations, drumlins, marginal features (moraine chains, abrupt margins, edges of ice-contact fans), ribbed moraines, tunnel valleys, eskers, geometrical ridge networks and hill-hole pairs. The dataset is accompanied by map presenting the dataset - Glacial geomorphology of the southern sector of the last Scandinavian Ice Sheet, central west Poland, that is produced in in PDF format and designed to be viewed at a scale of 1:500000. These data constitute a valuable source for reconstructing ice dynamics and constraining modelling of the southern sector of the last Scandinavian Ice Sheet, modelling the response of ice to climatic changes, and subglacial landform formation. These data allow comparison between subglacial landforms between localities, including both formerly glaciated and modern glaciated areas occupied by ice streams. : This work was supported by the Polish National Science Centre (NCN) under Grant [2015/17/D/ST10/01975]. Chris Clark and Stephen Livingstone were supported by the PalGlac project funded from the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (Grant agreement No. 787263)